Recruitment and plasmapheresis of donors to provide human antitetanus immunoglobulin. Issue 3 (March 1976) - Cook, I A; Ross, D W; Gordon, I
Abstract : A method is described whereby about 100 litres of plasma containing 10-50 IU/ml tetanus antitixin was obtained, from which were prepared 5000 X 250 IU doses of human antitetanus immunoglobulin. Of 40 blood donors who received a booster injection of tetanus vaccine BP, 33 were plasmapheresed each week over a 10-12 week period starting three weeks after the injection. Twenty-two of these donors provided 90% of the total plasma, the antitoxin content of which averaged 23.6 IU/ml over the 10-12 week period.